Date: Oct 21, 2012 8:20 AM
Author: Jose Carlos Santos
Subject: Ky Fan inequality
Hi all,

Please consider the Ky Fan inequality:

http://en.wikipedia.org/wiki/Ky_Fan_inequality

I tried to prove it directly (that is, without using some other

well-known inequality) by induction and already the first step was

harder than what I expected. This first step is: if 0 < a,b <= 1/2,

then

sqrt(ab)/sqrt((1 - a)(1 - b)) <= (a + b)/(2 - a + b)

What I did was to square both sides and then what I needed to prove

was that

(a + b)^2/(2 - a - b)^2 - ab/((1 - a)(1 - b)) >= 0.

So, I turned the LHS of this expression into a rational expression,

whose denominator is clearly >= 0 and whose numerator is

a^2 - a^3 + b^2 - b^3 + a^2b + ab^2 - 2ab. (*)

Since the original inequality is actually an equality when a = b, this

is also true for (*) and so I divided (*) by a - b, getting

a - a^2 - b + b^2 = a - b - (a^2 - b^2) = (a - b)(1 - a - b).

So, (*) = (a - b)^2(1 - a - b), which is clearly >= 0.

I have the feeling that what I did was too complicated. Can anyone see

a shorter way of proving this (again, avoiding the use of well-known

inequalities)?

Best regards,

Jose Carlos Santos